Comparative effects of aerobic walking and resistance exercise on cognitive function in older adults: A quasi-experimental study - Ganang Fandrian; Muchsin Dowes; Hanik Liskustyawati (Journal Sport Area)
Background: Cognitive decline threatens independence and quality of life in older adults. While exercise is recognized as a non-pharmacological strategy to preserve cognition, prior studies often neglect baseline cognitive function and rarely compare aerobic and resistance exercise. This gap limits understanding of which modality is more effective for maintaining cognitive health in later life. Research Objectives: This study aimed to determine the effects of aerobic walking exercise (AWE) and resistance exercise (RE) on cognitive function in older adults. Methods: A quasi-experimental pretest–posttest design was applied to 45 participants (23 males and 22 females), aged 60-69 years. The participants were allocated using an ordinal pairing technique to ensure comparable baseline scores, with 22 in the AWE group and 23 in the RE group. Both groups completed 24 exercise sessions over eight weeks (three times per week). Cognitive function was measured with the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) using a single-blind procedure. Data were analyzed using a paired t-test for within-group and one-way ANCOVA for between-group at a 5% significance level. Findings/Results: Both the AWE and RE groups showed significant improvements (P < 0.001) in MoCA-Ina outcome measures. There was a significant difference between the groups (P-value < 0.05), with a moderate effect size (ƞp² = 0.110). RE yielded a greater improvement (MoCA-Ina score increase of 2.21 points, 11.99%) than AWE (MoCA-Ina score increase of 1.27 points, 7.06%). Conclusion: RE provides a greater than AWE improvement in cognitive function in older adults. These findings support the incorporation of public health programs at community health centers, with adherence to appropriate exercise safety principles. Further research is required to confirm the impact on non-exercise participants, cultural applicability, and populations with comorbidities.